1998
DOI: 10.1523/jneurosci.18-24-10619.1998
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Excitation of Magnocellular Neurons in the Rat Hypothalamic Paraventricular Nucleus via Intranuclear Glutamatergic Circuits

Abstract: Noradrenergic projections to the hypothalamus play a critical role in the afferent control of oxytocin and vasopressin release. Recent evidence for intrahypothalamic glutamatergic circuits prompted us to test the hypothesis that the excitatory effect of noradrenergic inputs on oxytocin and vasopressin release is mediated in part by local glutamatergic interneurons. The voltage response to norepinephrine (30-300 M) was tested with whole-cell recordings in putative magnocellular neurons of the paraventricular nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
108
4
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 40 publications
20
108
4
1
Order By: Relevance
“…In a recent study, it was found that the NE-induced increase of excitatory postsynaptic potentials was blocked by ionotropic glutamate receptor antagonists. This result suggests that spike-mediated transmiter release in the hypothalamus resulted from presynaptic efect of NE on glutamate neurons [36].…”
Section: Direct Adrenergic and Glutamate Stimulation Of The Hypothalamusmentioning
confidence: 90%
See 1 more Smart Citation
“…In a recent study, it was found that the NE-induced increase of excitatory postsynaptic potentials was blocked by ionotropic glutamate receptor antagonists. This result suggests that spike-mediated transmiter release in the hypothalamus resulted from presynaptic efect of NE on glutamate neurons [36].…”
Section: Direct Adrenergic and Glutamate Stimulation Of The Hypothalamusmentioning
confidence: 90%
“…For example, the efect of hypothalamic NE on CRH release is mediated by intrahypothalamic glutamatergic interneurons [36]. Also, the activation of the HPA axis by electrical stimulation of the VNAB, or by direct PVN injection of, phenylephrine (an agonist with high ainity to α1-adrenergic receptors) was markedly inhibited by PVN administration of selective ionotropic glutamate receptor antagonists [37].…”
Section: Direct Adrenergic and Glutamate Stimulation Of The Hypothalamusmentioning
confidence: 99%
“…In these experiments, 30 M bicuculline (BIC) was bath applied to block inhibitory transmission. The chemical stimulation experiments were made by pressure application (10 -20 psi, 5-10 msec) (Picospritzer II; Parker-Hannefin, Fairfield, NJ) of a small microdrop of L-glutamate (5-10 mM) to the surface of the lateral hypothalamus, using a broken patch pipette of 50 -100 m tip diameter, as described previously (Belousov and van den Pol, 1997;Daftary et al, 1998;Smith and Dudek, 2001). These experiments were conducted in a slice preparation in which the lateral hypothalamic area was surgically isolated by cutting away and removing the rest of the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Noradrenergic effects on magnocellular PVN neurons were demonstrated to be the result of catecholamine actions on glutamate interneurons rather than direct effects on the magnocellular neuron itself [46]. Subsequently, a number of studies which have suggested important roles for glutamate interneurons in mediating the excitatory effects of ANG [25], orexin [33], and prokineticin 2 [47] on magnocellular neurons, capsaicin on preautonomic neurons [48], and on the response of neuroendocrine CRH neurons to restraint stress [49].…”
Section: Roles For Interneurons In the Regulation Of Pvn Output Neuronsmentioning
confidence: 99%